2023
DOI: 10.1126/sciadv.add5582
|View full text |Cite
|
Sign up to set email alerts
|

Human genetic history on the Tibetan Plateau in the past 5100 years

Abstract: Using genome-wide data of 89 ancient individuals dated to 5100 to 100 years before the present (B.P.) from 29 sites across the Tibetan Plateau, we found plateau-specific ancestry across plateau populations, with substantial genetic structure indicating high differentiation before 2500 B.P. Northeastern plateau populations rapidly showed admixture associated with millet farmers by 4700 B.P. in the Gonghe Basin. High genetic similarity on the southern and southwestern plateau showed population expansion along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…These findings were consistent with the premises of an eastern dispersal of taurine cattle along the Inner Asian Mountains and the Hexi Corridor and supported the genetic continuity of taurine cattle from the Bronze Age to the modern day but not a parallel movement of indicine cattle over the Himalayas. This observation agreed with recent human genomic evidence that suggested an extensive genetic admixture among the populations on the Tibetan Plateau and in East Asia ( 55 , 56 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings were consistent with the premises of an eastern dispersal of taurine cattle along the Inner Asian Mountains and the Hexi Corridor and supported the genetic continuity of taurine cattle from the Bronze Age to the modern day but not a parallel movement of indicine cattle over the Himalayas. This observation agreed with recent human genomic evidence that suggested an extensive genetic admixture among the populations on the Tibetan Plateau and in East Asia ( 55 , 56 ).…”
Section: Discussionsupporting
confidence: 91%
“…These haplogroups suggest a connection between highland ancient Tibetans and populations in the upper Yellow River region ( Ning et al, 2020 ; Xue et al, 2022 ; Zhang et al, 2023 ). D4j1a2 and D4j1b are common haplogroups in Lhasa Tibetans, and D4j1b can be found in ancient Zongri individuals ( Wang et al, 2023 ), revealing population movement from lower elevations to the TP between 4,750 and 2,775 years ago ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ST language family generally consists of Sinitic and TB, which are collectively spoken by approximately 1.5 billion native speakers. Evidence from the linguistic phylogeny, archaeology, and ancient DNA supported the northern-origin hypothesis, suggesting that the ancient populations speaking the proto-ST family and cultivating millet in the middle and upper Yellow River separated into two groups approximately 4–6 kya [ 51 , [65] , [66] , [67] , [68] , [69] ]. One group moved east and south of East Asia, spreading the Sinitic language, while the other group migrated to southwest East Asia, disseminating the TB language.…”
Section: Dynamic Demography Of Geographically Different East Asians S...mentioning
confidence: 97%
“…The evidence derived from the Y chromosome elucidates that the contemporary genetic makeup of TB-speaking populations can be traced to the predominant admixture of two groups in the Neolithic period. The hunter-gatherer populations initially settled on the Tibetan Plateau in the Paleolithic period with haplogroup D-M174 and ancient northern East Asians who migrated westward from the upper-middle Yellow River basin with haplogroups O2a2b1-M134 (xM117) and O2a2b1a1-M117 [ 12 , 69 , [86] , [87] , [88] ]. Further research showed that there might have been another Neolithic expansion of TB-speaking populations.…”
Section: Dynamic Demography Of Geographically Different East Asians S...mentioning
confidence: 99%